Neural Law and biometric technologies; An analysis of Invasiveness in the sphere of human life - Sánchez, Juan Diego Sánchez (2022)
This paper addresses the link between biometric technologies used for commercial and business research, their relation and their influence in personal and neuro behavioral sphere, highlighting the importance of the adjacent concepts of individual neuro-rights and the influence that the person could suffer from the invasiveness of these technologies. Considering an approach to biometric technologies, the data collected and their processing, these concepts are analyzed in the light of the privacy and intimacy sphere of the human being.